A comparative study of the structural and mechanical properties of avian eggshells among hosts of obligate brood parasitic cowbirds (genus Molothrus) - Lopez, Analia Veronica (2021)
Obligate avian brood parasites depend on hosts for parental care, which in turn suffer fitness losses as a result of parasitism. Mechanisms by which brood parasitic cowbirds (Molothrus spp.) reduce host breeding success include the puncture (M. rufoaxillaris and M. bonariensis) or removal (M. ater) of the eggs of the host. Our working hypothesis is that the host eggs' mechanical strength and their size and shape in species with higher frequency of parasitism covaries with the cowbird's strategy to reduce host clutch size. Our results, obtained through phylogenetic analyses based on egg 2D geometric morphometry and eggshell mechanical and ultrastructural measurements, suggest that egg-puncturer behaviour has led to an increase in the strength of the host's eggshell, which might make them more difficult to be pierced. We also characterized larger, more rounded and asymmetrical eggs in frequent hosts of M. ater, which might be more difficult to be removed. These interspecific host egg and shell traits were also positively affected by the frequency of parasitism, indicating that species-specific patterns of parasitic costs select for respective anti-parasitic defences in hosts.